Hamstring musculotendon dynamics during stance and swing phases of high-speed running - Chumanov, E. S.; Heiderscheit, B. C.; Thelen, D. G. (Medicine & Science in Sports & Exercise, 2011)
Introduction: Hamstring strain injuries are common in sports that involve high-speed running. It remains uncertain whether the hamstrings are susceptible to injury during late swing phase, when the hamstrings are active and lengthening, or during stance, when contact loads are present. In this study, we used forward dynamic simulations to compare hamstring musculotendon stretch, loading, and work done during stance and swing phases of high-speed running.